2017
DOI: 10.1002/epi4.12050
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the burden of focal epilepsy as a function of seizure frequency in the United States, Europe, and Brazil

Abstract: SummaryObjectiveTo understand the current burden of focal epilepsy (FE) as a function of seizure frequency.MethodsPatients were identified from the United States (2011, 2012, and 2013), five European countries (EU; France, Germany, Italy, Spain, United Kingdom) (2011 and 2013), and Brazil (2011 and 2012) National Health and Wellness Survey (NHWS), a nationally representative, Internet‐based survey of adults (18+ years). The NHWS collected data on respondents’ quality of life (QoL), health utilities, productivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Even though the NHWS is a nationally representative general population survey that uses stratified random sampling to recruit respondents, most respondents are recruited online. Nonetheless, several studies have shown that disease prevalence estimates and health outcome results reported from studies using NHWS data align with studies using non‐NHWS data 3,38–43 . All data collected are cross‐sectional in nature, so associations can be measured, but causality cannot be assessed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Even though the NHWS is a nationally representative general population survey that uses stratified random sampling to recruit respondents, most respondents are recruited online. Nonetheless, several studies have shown that disease prevalence estimates and health outcome results reported from studies using NHWS data align with studies using non‐NHWS data 3,38–43 . All data collected are cross‐sectional in nature, so associations can be measured, but causality cannot be assessed.…”
Section: Discussionmentioning
confidence: 94%
“…shown that disease prevalence estimates and health outcome results reported from studies using NHWS data align with studies using non-NHWS data. 3,[38][39][40][41][42][43] All data collected are cross-sectional in nature, so associations can be measured, but causality cannot be assessed. As is common in observational research, there is also the possibility of confounding by indication stemming from the selfreported nature of the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Full details of the study design and methods, including the survey instrument used, are published elsewhere [ 23 ]. Briefly, participants registered in existing opt-in online survey panels [Kantar Profiles (Lightspeed) global panel and its partners] [ 24 ] were invited to participate in a health survey without knowledge of the specific health topic. This study was performed in accordance with the Helsinki Declaration of 1964 and its later amendments.…”
Section: Methodsmentioning
confidence: 99%
“…Focal seizures (formerly known as partial seizures) constitute the most common seizure type, representing up to 61% of the epilepsy population (Gupta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is one of the most common neurological conditions; it affects people of all ages, races, social classes, and geographical locations. Focal seizures (formerly known as partial seizures) constitute the most common seizure type, representing up to 61% of the epilepsy population (Gupta et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%